MOBILE TECHNOLOGIES IN VIRTUAL LEARNING ENVIRONMENTS - Tkach Г.; Kerimbayev Н.Н.; Nurym Н.Н.; Akramova А.С. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
The issues and problems of mobile learning in virtual environments have gained widespread academic and commercial recognition in recent years. Although the evolution of wireless technologies and the number of mobile applications is impressive, the issues of widespread use of mobile technologies in virtual learning environments are not well represented. Immersive digital technologies, which are spreading in all spheres of human life, are increasingly being introduced into the educational environment. Mobile technologies in the learning process have become the subject of much modern research. This article describes the design of a training system consisting of mobile technologies used in virtual environments. This work makes an attempt to show the change in the mechanisms of functioning and implementation of the education system in the conditions of virtual learning environments. It is expected that the proposed work will make the organization of virtual learning effective, practical and ergonomic, provide a learning process aimed at mastering the result. Mobile technologies are technical support for the learning virtual environment, under the influence of which significant changes occur in the process of assimilating knowledge, implementing mobile, highly effective feedback.